2016
DOI: 10.1016/j.celrep.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Liver ERα in Coupling Hepatic Metabolism to the Reproductive Cycle

Abstract: SummaryLipoprotein synthesis is controlled by estrogens, but the exact mechanisms underpinning this regulation and the role of the hepatic estrogen receptor α (ERα) in cholesterol physiology are unclear. Utilizing a mouse model involving selective ablation of ERα in the liver, we demonstrate that hepatic ERα couples lipid metabolism to the reproductive cycle. We show that this receptor regulates the synthesis of cholesterol transport proteins, enzymes for lipoprotein remodeling, and receptors for cholesterol u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 32 publications
10
106
0
Order By: Relevance
“…Using a mouse model with ERα-deficiency in hepatocytes, we demonstrated that the ability of estrogens to reduce liver steatosis is lost in with deletion of liver ERα, suggesting that estrogens are acting directly in liver to reduce TG content through ERα (Palmisano et al 2016; Zhu et al 2013; Villa et al 2012). As expected, loss of liver ERα results in increased expression of lipid synthesis genes (Bryzgalova et al 2006), loss of estrogen regulation of target genes (Palmisano et al 2016; Zhu et al 2013), and impaired estrogen regulation of other lipid metabolic target genes (Della Torre et al 2016). One proposed mechanism for ERα regulation of lipid synthesis targets involves estrogen-ERα regulation of the nuclear receptor Small Heterodimer Partner (SHP), a target gene of ERα (Palmisano et al 2016; Wang et al 2015).…”
Section: Estrogens and The Physiologic Regulation Of Liver Lipid Metasupporting
confidence: 61%
“…Using a mouse model with ERα-deficiency in hepatocytes, we demonstrated that the ability of estrogens to reduce liver steatosis is lost in with deletion of liver ERα, suggesting that estrogens are acting directly in liver to reduce TG content through ERα (Palmisano et al 2016; Zhu et al 2013; Villa et al 2012). As expected, loss of liver ERα results in increased expression of lipid synthesis genes (Bryzgalova et al 2006), loss of estrogen regulation of target genes (Palmisano et al 2016; Zhu et al 2013), and impaired estrogen regulation of other lipid metabolic target genes (Della Torre et al 2016). One proposed mechanism for ERα regulation of lipid synthesis targets involves estrogen-ERα regulation of the nuclear receptor Small Heterodimer Partner (SHP), a target gene of ERα (Palmisano et al 2016; Wang et al 2015).…”
Section: Estrogens and The Physiologic Regulation Of Liver Lipid Metasupporting
confidence: 61%
“…As it is known that in females estrogens directly regulate large part of the genes above mentioned, the differential expression reported may be explained by the fact that, contrary to females, males have low circulating levels of estrogens, in the liver do not expressed the enzyme synthesizing estrogens from testosterone (aromatase) (Granata et al, 2009;Harada et al, 1993), and have an hepatic content of ER protein 3-5 fold lower than females (Della Torre et al, 2016). In mammals, however, other mechanisms regulating liver functions were established with evolution; first of all, the brain is sexually differentiated by the activity of male gonads in a window of time that occurs around birth.…”
Section: Liver Sexual Dimorphism a Resultant Of Evolutionary Pressure?mentioning
confidence: 99%
“…In addition, studies in female mouse showed a specific synchrony of ER transcriptional activity in liver and reproductive tissues (Ciana et al, 2003;Della Torre et al, 2011a) with a rhythm imposed by the reproductive cycle. In this interplay, nutrient uptake was shown to be essential to maintain liver ER activity (Ciana et al, 2005;Della Torre et al, 2016;Della Torre et al, 2011b;Villa et al, 2012).…”
Section: The Mechanisms Subjecting Fertility To Nutrient Availabilitymentioning
confidence: 99%
See 2 more Smart Citations